TOXIC EFFECTS OF 2.5% SODIUM HYPOCHLORITE, 17% ETHYLENEDIAMINETETRAACETIC ACID, AND 2% CHLORHEXIDINE SOLUTIONS ON THE VIABILITY OF DENTAL PULP MESENCHYMAL STEM CELLS - MUSTIKASARI, BUNGA CAHYA; MARGONO, ANGGRAINI; NAZAR, KAMIZAR (International Journal of Applied Pharmaceutics, 2019)
Objective: Disinfection of the root canal system is a key factor in the success of regenerative endodontic treatment. However, dental irrigation solutions must exert bactericidal effects while maintaining stem cell viability. This study aimed to compare the effects of solutions containing 2.5% sodium hypochlorite, 17% ethylenediaminetetraacetic acid, and 2% chlorhexidine on the viability of dental pulp mesenchymal stem cells. Methods: Primary cells were obtained from immature third molars and cultured. Subsequently, an immunofluorescence assay specific for the mesenchymal stem cell marker STRO-1 was used to identify dental pulp mesenchymal stem cells in the cultures. These cells were exposed to the three above-described solutions, after which cell viability was analyzed using an 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) assay. Results: The viabilities of dental pulp mesenchymal stem cells treated with the three irrigating solutions differed significantly from the viability of control cells (P ≤ 0.05). However, no significant differences in cell viability were observed among the solutions (P ≥ 0.05). Conclusion: All tested solutions had toxic effects on the viability of dental pulp mesenchymal stem cells.